PENGARUH LITERASI KEUANGAN, PERILAKU KEUANGAN, DAN PENGETAHUAN INVESTASI TERHADAP MINAT BERINVESTASI: STUDI EMPIRIS KARYAWAN SWASTA DI KECAMATAN WANASARI - Winani Oktaviani; Hilda Kumala Wulandari; Titi Rahmawati (Jurnal Bina Bangsa Ekonomika, 2023)
This study aims to determine the influence of financial literacy, financial behavior and investment knowledge on investment interest in Wanasari District. The type of research used is quantitative descriptive research method. The type and source of data used is primary data collected and processed by the researcher himself from the object. The population in the study was 2,652 private employees. The sampling technique uses probability sampling with a type of simple random sampling. This research was conducted by distributing questionnaires to 348 respondents from private employees in Wanasari District. The analytical technique data used in this study are descriptive statistical test, classical assumption test, multiple linear regression test, t test, F test and coefficient of determination with the help of SPSS software program. The results of this study show that financial literacy has a positive and significant effect on investment interest, financial behavior has a positive and significant effect on investment interest, investment knowledge has a positive and significant effect on investment interest, and financial literacy, financial behavior, and investment knowledge have a positive and significant effect on investment interest